On the Uncertain Future of Work and the Role of Social Actors - Martínez, Daniel (2018)
There is some consensus that technological changes bring about important changes in the organization of production and work: 1) technological changes cause job losses (the opportunity costs of incorporating machines are advantageous compared to those of not replacing labor) but also job creation, making it difficult to predict the net balance in each country; 2) in many cases, the effect of technological changes is not only the loss/creation of jobs, but the disappearance/creation of crafts and trades; 3) besides these quantitative effects, technological changes and the reorganization of forms of production result in the emergence of new, unconventional ways of using labor that are not easily adapted to current regulations; 4) household poverty is reduced, but inequality increases within domestic labor markets, as well as between the labor markets of different countries. This study will analyse all of these aspects. Section 2 summarizes the qualitative and quantitative effects of these changes on employment and the composition of the occupational structure, as well as new ways of using labor and increasing inequality in the labor market. Section 3 presents some reflections on changes in labor relations and the challenges they pose to labor regulations and the role of social actors